Response of Some Productive Traits of Broiler Chickens to Magnetic Water - Alhassani , D.H.; Amin, G.S. (International Journal of Poultry Science, 2012)
Magnetic drinking water (MW) technology has recently been found many advantages, in particular on poultry performance. This study examined the effect of MW on some productive traits of broiler chickens during 1-42 days old. A total of 300 day-old unsexed broiler chicks (Cobb-500) were randomly assigned into 4 treatments of 5 replicates each (20 birds/replicate). Birds were housed in cages. Treatments T1, T2 and T3 means that birds received MW which being passed by magnetizer device (500 gause) with speeds 5, 10 and 15 min respectively to obtain 10 letters MW, whereas T4 ( control ) received tap water. Results of studied traits (body weight, weight gain, feed intake, feed conversion ratio, mortality, viability and production index) generally exhibited no significant differences between MW treatments (T1, T2 and T3) and T4. Despite of the fluctuation in results, however MW treatments revealed their superiority on T4, in particular T3.